2019
DOI: 10.1109/access.2019.2914352
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Routing Problem for Ground Vehicle and Unmanned Aerial Vehicle: The Application on Intelligence, Surveillance, and Reconnaissance Missions

Abstract: In this paper, we investigate a novel two-echelon ground vehicle and its mounted unmanned aerial vehicle cooperative routing problem (2E-GUCRP) for intelligence, surveillance, and reconnaissance (ISR) missions. In a typical cooperative system with ground vehicle (GV) and unmanned aerial vehicle (UAV), the UAV is launched from the GV, automatically flies to the designated target and return to the GV before powering off. Meanwhile, acting as a mobile platform, the GV can carry the UAV moving in a larger region a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…However, only a few studies demonstrated how to deploy UAVs in specific battlefields for cooperative mission planning. Due to the limitation of current hardware and technical conditions, how to reasonably dispatch UAVs to perform cooperative tasks and choose the best reconnaissance route for a group or cluster of UAVs is of great significance to operations [7,8].…”
Section: The Multi-unmanned Aerial Vehicle (Uav) Systemmentioning
confidence: 99%
“…However, only a few studies demonstrated how to deploy UAVs in specific battlefields for cooperative mission planning. Due to the limitation of current hardware and technical conditions, how to reasonably dispatch UAVs to perform cooperative tasks and choose the best reconnaissance route for a group or cluster of UAVs is of great significance to operations [7,8].…”
Section: The Multi-unmanned Aerial Vehicle (Uav) Systemmentioning
confidence: 99%
“…Each customer can be served only once by only one vehicle. To the best of our knowledge, there are a variety of optimal and heuristic algorithms to MVRPSDP problems in the existing literature [24]- [26], [37]- [39]. In this study, we apply the state-ofthe-art MIP resolver tool, ILOG-CPLEX (version 12.80) to efficiently resolve the relaxed model with Constraints (4)- (10) and (12) and obtain the optimal routes for vehicles.…”
Section: Subalgorithm In the Second Stagementioning
confidence: 99%
“…The number of applications for unmanned aerial vehicles (UAVs) is widely increasing in the civil arena such as surveillance [1,2], delivery of goods [3,4], power line inspection [5,6], and mapping [7,8].…”
Section: Introductionmentioning
confidence: 99%